Periprocedural outcomes of transcatheter aortic valve replacement (TAVR) in patients with and without cardiac amyloidosis-analysis from 2016–2019 national inpatient sample. (3rd October 2022) - Kambalapalli, S; Baral, N; Seri, A; Paul, T
Abstract: Background: Cardiac Amyloidosis is often misdiagnosed due to its non-specific presenting symptoms. There is a lack of evidence on the clinical outcomes in patients with cardiac amyloidosis undergoing transcatheter aortic valve replacement (TAVR). Purpose: To study periprocedural outcomes in patients hospitalised primarily for TAVR with and without cardiac amyloidosis. Methods: This is a retrospective observational study involving index hospitalizations for TAVR between January 1, 2016 to December 31, 2019 from the National Inpatient Sample (NIS), the largest all-payer public database of hospital care data in the United States. Our study sample included discharged adult patients (≥18 years) primarily hospitalised for TAVR using ICD-10 codes. Confounders were adjusted using multivariable regression analysis. Results: During 2016–2019, there were 43270 principal hospitalizations (unweighted sample) identified for TAVR, among them 4999 patients had a history of cardiac amyloidosis. Mean age was 79.3±8.4 years. Among patients hospitalised for TAVR, 54.4% (n=23539) were males, 45.6% (n=19731) were females (p<0.001), 1.71% (n=740) developed cardiogenic shock, 1.53% (n=662) required mechanical ventilation with an in-hospital mortality of 1.3% (n=563). There were 87% Whites, 4.2% Blacks, 4.8% Hispanics, 1.3% Asians, and 2.7% were other races. A total of 23, 819 (55.1%) hospitalizations had a Charlson Comorbidity Index (CCI) of three or higher. After undergoing TAVR, compared to the non-cardiac amyloidosis cohort, the cardiac amyloidosis cohort had less females (27.8% vs 45.6%, p=0.01), had similar age (mean age: 80.2 vs 79.3; p=0.665), higher incidence of congestive heart failure (CHF) (100% vs 74%, p=0.012), higher mechanical ventilation requirement (11.1% vs 1.5%, p=0.001)) but with a similar length of hospital stay (3.9% vs 3.9%, p=0.99). Multivariate regression analysis revealed that TAVR in cardiac amyloidosis cohort did not significantly increase the odds of in-hospital mortality than the non-cardiac amyloidosis cohort (aOR: 5.2; 95% CI: 0.7, 38.3; p=0.103). However, females had higher odds of mortality post-TAVR compared to males (aOR: 1.45; 95% CI: 1.22, 1.73; p<0.001) after controlling for age, sex, race, regional hospital location, hospital bed capacity, income, and CCI. There is an increasing trend of index TAVR hospitalizations with cardiac amyloidosis with 109.4 per 100, 000 hospitalizations in 2016, 139.7 per 100, 000 in 2017, 157.5 per 100, 000 in 2018, 201.4 per 100, 000 in 2019 (p trend<0.001). Conclusions: After TAVR, cardiac amyloidosis is associated with higher incidence of CHF increased need for mechanical ventilation, similar in-hospital mortality rate in comparison to non-cardiac amyloidosis cohort. There was an increasing trend in the index hospitalizations for TAVR with cardiac amyloidosis from 2016–2019. Funding Acknowledgement: Type of funding sources: None.